2022
DOI: 10.1038/s41398-022-02006-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic clomipramine treatment increases hippocampal volume in rats exposed to chronic unpredictable mild stress

Abstract: It is well known that neuroinflammation is closely related to the pathophysiology of depression. Due to individual differences in clinical research, the reduction of hippocampal volume in patients with depression is still controversial. In this experiment, we studied a typical kind of tricyclic antidepressant, clomipramine. We designed a series of experiments to find its role in depressive-like behavior, hippocampal neuroinflammation as well as hippocampal volume changes induced by chronic unpredictable mild s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…A video tracking system (SMART 3.0, Spain) was used to videotape the total activity of the mice for 5 min, during which time the mice were allowed to move freely. The data on the time spent in the central area and the total distance traveled were collected from the video (Zhang et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A video tracking system (SMART 3.0, Spain) was used to videotape the total activity of the mice for 5 min, during which time the mice were allowed to move freely. The data on the time spent in the central area and the total distance traveled were collected from the video (Zhang et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…A combination of genetic, neurological, and psychological factors contribute to the overall risk of depression (Zhang et al., 2022 ). A family history of depression, early life neglect and abuse, life stress, and comorbid physical illnesses all increase the risk of depression (Beurel E et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Zhang et al. found that clomipramine modulated the microglial NLRP3 inflammasome to reduce depressive behavior and increase hippocampal volume in exposure to CUMS model of rats ( 204 ). Meanwhile, amitriptyline was found to inhibit LPS-induced microglial expression of pro-inflammatory factors ( 205 ) and increase BDNF expression in microglia ( 206 ).…”
Section: Drugs Targeting Microglia To Alter Neurogenesis For Treating...mentioning
confidence: 99%
“…Currently, SSRIs are the first line of antidepressants used in clinical practice. This category includes sertraline, paroxetine, fluvoxamine, fluoxetine, citalopram, and escitalopram, which selectively inhibit 5-HT reuptake by antagonistically binding presynaptic membrane 5-HT transporters in neurons, thus increasing the concentration of 5-HT in the synaptic cleft ( 204 , 210 ). Previous studies have shown that adult neurogenesis and olfactory memory are positively regulated by fluoxetine.…”
Section: Drugs Targeting Microglia To Alter Neurogenesis For Treating...mentioning
confidence: 99%